Extraction of oil from sunflower (Helianthus Annuus) seed by solvent extraction method: article / Nur Farahin Zakaria and Faiznur Mohd Fuad - Zakaria, Nur Farahin; Mohd Fuad, Faiznur (2019)
This research was conducted to determine the optimum percentage of oil yield from the sunflower seed through Solvent Extraction method. The oil yield was determine by using one parameter at one time method (OFAT). Four parameters has been tested in this method which are the type of solvent used, effect of temperature, effect of time, and the solid to liquid ratio. Then, the oil collected was tested by using the Gas Chromatography-Mass Spectrum machine (GCMS) to identify the chemical constituent consist in the oil. According to the result, the optimum oil yield is 60.4% of oil has been extracted by using Ethyl acetate as the solvent. For the effect of temperature, the optimum oil yield was collected at temperature 40°C, while for the effect of time, the optimum yield was collected at time 15 minute. As for the solid to liquid ratio, the optimum percentage of oil yield obtain is 60.4% which the ratio used are 10:1.